P 159 Long-time course of idiopathic small fiber neuropathy. Issue 10 (October 2017) - Floßdorf, P.; Haupt, W.F.; Brunn, A.; Fink, G.R.; Wunderlich, G.
Abstract : Background: Small fiber neuropathy (SFN) represents a subtype of peripheral neuropathies. As only small A-delta and C-fibers are involved patients suffer from typical clinical symptoms such as hypesthesia, burning and prickling sensations, temperature disturbance perception or autonomic symptoms without any signs of large fiber involvement. Thus electrophysiological examinations (sensory and motor nerve conduction studies (NCS), electromyography (EMG) and evoked potentials (EP)) do not elicit pathological findings as they indicate large fiber involvement. A reduced intraepidermal nerve fiber density can be demonstrated via skin biopsy. As there are several causes for small fiber damage SFN also may represent an early stage of other neuropathies with progression to large fiber neuropathy over time. If no underlying cause can be detected, the diagnosis of "idiopathic" SFN can be made. The prevalence of idiopathic SFN not converting into a mixed neuropathy over time is unknown. To address this question, we followed the long-term clinical course of idiopathic SFN-patients. Patients and methods: We studied 19 patients with idiopathic SFN retrospectively. In all patients a symptomatic cause was excluded by extensive laboratory examination and repeated electrophysiological examination (NCS, EMG, EP). Skin biopsy was performed in all patients to verify intraepidermal nerve fiber density. The observation period ranged from 2.5 to 14 years from symptom onset. Results: In 19 patients an idiopathic SFN was diagnosed. All of them showed reduced intraepidermal nerve fiber density. At the time of diagnosis and in long-term follow-up all patients suffered from typical clinical symptoms such as (thermal-) hypaesthesia, burning sensations, pain, reduced vibration sense and prickling. Seven patients were lost to follow-up. Three showed disease progression in terms of large fiber involvement, in nine patients clinical and electrophysiological parameters remained stable over time. Discussion/Conclusion: We demonstrated that in long-term course of idiopathic SFN 75% of the patients remained in stable condition while only 25% developed other neuropathies. These findings are well in line with the results of Devigili et al., who also revealed the same amount in a two year follow-up. Although SFN is usually diagnosed mainly by exclusion, there are various diagnostic procedures to support or confirm the diagnosis. Verifying a reduced intraepidermal nerve fiber density via skin biopsy represents the "gold standard". Other examinations, such as quantitative sensory testing (QST) or quantitative sudormotor axonal reflex (QSART) are helpful but should not be used as the only test to establish the diagnosis of SFN. Once the diagnosis of idiopathic SFN is defined, routine clinical and electrophysiological examinations should be applied to distinguish between stable idiopathic SFN-patients and those who develop other neuropathies. Since causal therapy does not exist so far we emphasize that every patient with SFN should be treated symptomatically, especially to reduce neuropathic pain.